METHODS OF LEASING OPERATIONS EFFICIENCY EVALUATION - KYSHAKEVCYH, BOHDAN; MIGULKA, OLGA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes modern approaches to assessing the effectiveness of leasing operations both from the side of the lessor and from the side of the lessee. It was shown that in this area there is no unambiguity in the choice of methodology that should be used to assess leasing investments. It is argued that due to the fact that leasing is always more expensive than a regular purchase and sale transaction, not all entrepreneurs understand the advantages of this unconventional method of productive investment, since the additional profit received from the turnover of capital freed up through the use of leasing is not taken into account. There are also conflicting aspects of the legal regulation of the leasing business. It is shown that the most common method for assessing the effectiveness of leasing operations is an approach based on assessing the effectiveness of leasing in comparison with a type of active operations similar in economic essence - bank loans. The lessee, based on a comparison of the interest on the lease, which he will be obliged to pay to the lessor under the terms of the lease agreement, with the bank credit rate, may decide what will be of great economic benefit for him: to accept a lease agreement or to acquire property on credit. The disadvantages of leasing in comparison with lending can be attributed to its higher cost, since lease payments must compensate for the depreciation of property, the cost of invested resources and interest for servicing the buyer. However, the popularity of leasing is due to the fact that it is an effective method for accelerating the renewal of fixed assets. The lessee, based on a comparison of the lease interest with the bank lending rate, can make a decision - what will be of great economic benefit for him: to accept a leasing agreement or to acquire property on credit.
Keywords: leasing operations; leasing efficiency; lessee; lessor; bank credit; lease payments; DEA analysis